Preference for Prestige: Commentary on the Behaviour of Universities and their Benefactors - Caton, Charlotte S. (Canadian Journal of Higher Education, 2017)
This paper examines institutional behaviour, as perceived and described by individuals who have donated large gifts to private non- profit (not-for-profit) corporations especially universities. The study improves the understanding readers may have of the means used by Canadian institutions to initiate relationships with individuals capable of making large gifts, of how these relationships are nurtured, of who in the organization influences decisions about the purposes served by gifts from these donors and of how institutional and/or personal prestige are factors in donor-recipient relationships. More significantly, the study explores the degree to which institutions involve major donors as partners in enhancing an institution's reputation for quality. Data reported here were gathered from interviews with donors to universities, hospitals and arts organizations in Toronto. The responses of donors are reported and some differences identified between donors to universities and donors to either hospitals or arts organizations. With the largest generational transfer of wealth in history starting to occur, the findings may prove useful to universities as they compete for charitable dollars with other nonprofit organizations.